The Effectiveness of Implementing Sign Language in the College Environment in Denpasar City - Karuniati, Ni Nengah; Yowana, I Made Adiwidya; Juniasa, I Dewa Nyoman; Umbas, Ronald; Sugiantiningsih, Anak Agung Putu (JIHAD : Jurnal Ilmu Hukum dan Administrasi, 2025)
In the era of digitalization, the use of sign language in social contexts is increasingly prevalent in Bali, especially as a center for disability communities, particularly for the hearing impaired. It has even become a potential resource, as the strengths that accompany their challenges can offer unique advantages both academically and non-academically. This paper elaborates on the use of sign language at universities in Denpasar. According to regulations that ensure access for individuals with disabilities to attend higher education, such as the Minister of Research, Technology, and Higher Education Regulation No. 46 of 2017 regarding Special Education and Special Service Education in Higher Education, the Law on Persons with Disabilities No. 8 of 2016, and the Republic of Indonesia Law No. 20 of 2003 on the National Education System, universities are obligated to: not reject students with disabilities from studying on their campuses, provide appropriate facilities and infrastructure for students with special needs, and implement policies that allow eligible individuals with disabilities to participate in educational processes easily, comfortably, and safely. Higher education institutions can take various actions to support students with disabilities. They are even encouraged to establish Disability Service Units (DSUs) for hearing-impaired students. Universities are striving to implement the use of sign language. However, it cannot yet be fully concluded that a mandatory course on sign language is necessary; this requires a lengthy process and thorough study for effective implementation.